Lipid droplets in the nervous system - Ralhan, Isha; Chang, Chi-Lun; Lippincott-Schwartz, Jennifer; Ioannou, Maria S (The Journal of cell biology, 2021)
Lipid droplets are dynamic intracellular lipid storage organelles that respond to the physiological state of cells. In addition to controlling cell metabolism, they play a protective role for many cellular stressors, including oxidative stress. Despite prior descriptions of lipid droplets appearing in the brain as early as a century ago, only recently has the role of lipid droplets in cells found in the brain begun to be understood. Lipid droplet functions have now been described for cells of the nervous system in the context of development, aging, and an increasing number of neuropathologies. Here, we review the basic mechanisms of lipid droplet formation, turnover, and function and discuss how these mechanisms enable lipid droplets to function in different cell types of the nervous system under healthy and pathological conditions.